2017
DOI: 10.1111/acer.13508
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Induced Behaviors Require a Subset of Drosophila JmjC‐Domain Histone Demethylases in the Nervous System

Abstract: Background Long-lasting transcriptional changes underlie a number of adaptations that contribute to alcohol use disorders (AUD). Chromatin remodeling, including histone methylation, can confer distinct, long-lasting transcriptional changes, and histone methylases are known to play a role in the development of addiction. Conversely, little is known about the relevance of Jumonji (JmjC) domain-containing demethylases in AUDs. We systematically surveyed the alcohol-induced phenotypes of null mutations in all 13 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 50 publications
(67 reference statements)
0
50
0
Order By: Relevance
“…In the past 2 years, 3 alcohol studies from different Drosophila groups have identified a set of histone-modifying enzymes with direct roles in controlling adaptive alcohol responses. 60 62 These findings, reviewed below, have strengthened the link between epigenetic modifications and alcohol-induced neuroadaptations and have solidified the importance of the Drosophila model in elucidating the mechanisms of alcohol addiction.…”
Section: Drosophila Paves the Waymentioning
confidence: 92%
See 1 more Smart Citation
“…In the past 2 years, 3 alcohol studies from different Drosophila groups have identified a set of histone-modifying enzymes with direct roles in controlling adaptive alcohol responses. 60 62 These findings, reviewed below, have strengthened the link between epigenetic modifications and alcohol-induced neuroadaptations and have solidified the importance of the Drosophila model in elucidating the mechanisms of alcohol addiction.…”
Section: Drosophila Paves the Waymentioning
confidence: 92%
“…In Drosophila , there are at least 13 JmjC-KDMs each with different substrate specificity. 80 In a recent study, Pinzón et al 62 systematically tested the role of all known Drosophila JmjC-KDM in alcohol-induced responses. They focused on 2 main alcohol-related behaviors: innate sensitivity and rapid tolerance.…”
Section: The Jmjc-domain Histone Demethylasesmentioning
confidence: 99%
“…To date, over 91 genes in Drosophila and over 50 genes in C. elegans have been identified that regulate EtOH‐induced behaviors (reviewed by Grotewiel and Bettinger, ). The list of genes in Drosophila includes genes involved in the regulation of processes, such as learning and memory, circadian rhythm, innate immune defense, and the blood–brain barrier; on a cellular level, these effects extend to the regulation of the cell cycle, neuronal activity, synaptic function, axonal transport, insulin signaling, immediate early response on transcriptional level, cytoskeleton dynamics, chromosome dynamics, cellular stress responses, and intracellular detoxification of endogenous and xenobiotic substrates (Adhikari et al., ; Choi et al., ; Iacobucci and Gunawardena, ; Morozova et al., ; Parkhurst et al., ; Pinzon et al., , among others; for review, see also Park et al., ).…”
Section: Studying the Action Of Etoh: Characteristics Of Etoh‐inducedmentioning
confidence: 99%
“…As a notable alternative to typical transcriptomics, two groups performed ChIP-seq on post-mortem samples to show that, like gene expression, histone methylation is altered in the brains of alcoholics [10,169]. These studies supported later fly research that revealed a role of various histone demethylases in alcohol responses [121]. Given that covalent epigenetic markers are more stable than mRNA, there is great potential for epigenome studies in this context, though these approaches are still in their infancy [10].…”
Section: Transcriptomics On Post-mortem Human Tissuementioning
confidence: 94%
“…For example, global expression of a protein kinase A (PKA) inhibitor causes sensitivity to alcohol sedation [114], while anatomically limited inhibition causes resistance or sensitivity, depending on the neuroanatomical locus [65,114]. Many studies demonstrate the utility of these Drosophila genetic tools to establish causal roles of various genes in alcohol phenotypes, including many linked to specific cell populations [31,66,101,[115][116][117][118][119][120][121]. The split-Gal4 system permits even further refinement by limiting manipulations to subsets defined by two criteria (e.g., GABAergic neurons in the ellipsoid body) [122], thus allowing investigation into the contribution of neuronal subpopulations or even individual neurons to the development of alcohol abuse disorders ( Figure 1).…”
Section: Advantages Of Using Flies For Aud Researchmentioning
confidence: 99%